2004
DOI: 10.1038/nm1119
|View full text |Cite
|
Sign up to set email alerts
|

S-Glutathiolation by peroxynitrite activates SERCA during arterial relaxation by nitric oxide

Abstract: Nitric oxide (NO) physiologically stimulates the sarco/endoplasmic reticulum calcium (Ca(2+)) ATPase (SERCA) to decrease intracellular Ca(2+) concentration and relax cardiac, skeletal and vascular smooth muscle. Here, we show that NO-derived peroxynitrite (ONOO(-)) directly increases SERCA activity by S-glutathiolation and that this modification of SERCA is blocked by irreversible oxidation of the relevant cysteine thiols during atherosclerosis. Purified SERCA was S-glutathiolated by ONOO(-) and the increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
547
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 581 publications
(578 citation statements)
references
References 45 publications
21
547
1
5
Order By: Relevance
“…Oxidative stress has been shown to result in oxidative damage to functional proteins [35]. SERCA2a has been shown to be a vulnerable target for oxidative insult [27,36]. In this study we demonstrated a marked oxidative modification of SER CA2a in Lep/Lep mouse myocytes, which may contribute to reduced SERCA activity and subsequent cardiac contractile dysfunction in Lep/Lep mouse myocytes.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Oxidative stress has been shown to result in oxidative damage to functional proteins [35]. SERCA2a has been shown to be a vulnerable target for oxidative insult [27,36]. In this study we demonstrated a marked oxidative modification of SER CA2a in Lep/Lep mouse myocytes, which may contribute to reduced SERCA activity and subsequent cardiac contractile dysfunction in Lep/Lep mouse myocytes.…”
Section: Discussionsupporting
confidence: 49%
“…Filters were then removed from the manifold, placed in scintillation fluid and counted. SERCA activity was expressed as cpm/mg protein [27].…”
Section: Serca Isoenzyme 2a Immunoprecipitation and Protein Carbonyl mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even in vascular smooth muscle, a significant component of the relaxation response may be cGMP independent. In some vessels and species, the response may even be completely independent of cGMP [5][6][7][8], and it has been shown that animals deficient in a SNO-metabolizing enzyme have low vascular resistance ( [9], JSS unpublished). By analogy, stringent genetic evidence for a role of NO (per se) in blood pressure control has not been provided.…”
Section: Oxidants As Modulators Of Signal Transductionmentioning
confidence: 99%
“…However, although these studies suggested peroxynitrite was responsible for the S-nitrosation of SERCA they did not measure disulfide formation [41]. Prior to these S-nitrosation-focused studies, peroxynitrite was shown to directly increase SERCA-dependent Ca 2+ uptake activity due to a disulfide, namely S-glutathiolation of Cys-674 [118]. During atherosclerosis Cys-674 was oxidised to a sulfonic acid, preventing Sglutathiolation and limiting SERCA activity, illustrating the functional importance of disulfide in the control of SERCA activity.…”
Section: Sarco/endoplasmic Reticulum Ca2+-atpasementioning
confidence: 99%